Efeitos da intervenção de enfermagem-relaxamento no sistema imunológico das puérperas - Primo, Cândida Caniçali (2005)
This study examine the influence of Nursing Intervention – Relaxation on the immune system of postpartum women. 60 women (control and experimental group) were recruited from the postpartum floor of Cel. Leôncio Vieira de Resende Maternity in Serra, Espírito Santo. Research the secretory IgA levels in the postpartum women and the correlations with age, hours postpartum, partum, tobacco and alcohol use, anxiety and depression. Use an interview, State Trait Anxiety Inventory, and Edinburgh Postnatal Depression Scale. IgA was dosed using immuneturbidimeter and was collected in two moments: until 24 hours postpartum and one week later. The data was analyzed by the Social Package Statistical Science called SPSS version 8.0 – 1997. Conclusions: the Nursing Intervention – Relaxation increase the secretory IgA levels and reduce anxiety postnatal in the postpartum women of experimental group. No correlations were found.